Pembuatan Taman Vertikal dan Video Promosi Wisata Telaga Madiredo Kecamatan Pujon Kabupaten Malang - Alif Achadah; Hasan Bisri; Novita Fadia Rahma P (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Group 09 of thematic real work lectures (KKN-T) at Raden Rahmat Islamic University Malang took a superior program, namely tourism development. The tourism development taken is in the Telaga Madiredo agrotourism. Madiredo Lake Agrotourism is a tourist attraction that carries a natural theme found in Madiredo Village, Pujon District, Malang Regency. The developments made at Telaga Madiredo include video promotion and the creation of a vertical garden. Making this vertical garden uses natural materials found around the village, namely bamboo. The aim of making this video promotion is to make tourists in the Malang area and outside Malang City aware of and attract tourists to visit.